2021
DOI: 10.1155/2021/6611126
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Autophagy: A Novel “Rejuvenation” Strategy for the Aging Liver

Abstract: Aging is a natural life process which leads to a gradual decline of essential physiological processes. For the liver, it leads to alterations in histomorphology (steatosis and fibrosis) and function (protein synthesis and energy generation) and affects central hepatocellular processes (autophagy, mitochondrial respiration, and hepatocyte proliferation). These alterations do not only impair the metabolic capacity of the liver but also represent important factors in the pathogenesis of malignant liver disease. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 307 publications
0
5
0
1
Order By: Relevance
“…Based on various studies on the impact of the autophagy pathway on NAFLD, it is demonstrated that autophagy is closely associated with NASH progression via several factors that either promote or inhibit the autophagy pathway. The downregulation of autophagy is observed in many circumstances that favor NASH, such as increased insulin levels [ 19 ], obesity [ 20 ], the increased consumption of lipids [ 20 , 21 ], as well as aging [ 22 ] and the overabundance of stored lipids in the liver. The downregulation of the pathway is estimated via the assessment of LC3II and autophagosomes, as well as the number of autophagolysosomes.…”
Section: The Association Between Autophagy and Nashmentioning
confidence: 99%
“…Based on various studies on the impact of the autophagy pathway on NAFLD, it is demonstrated that autophagy is closely associated with NASH progression via several factors that either promote or inhibit the autophagy pathway. The downregulation of autophagy is observed in many circumstances that favor NASH, such as increased insulin levels [ 19 ], obesity [ 20 ], the increased consumption of lipids [ 20 , 21 ], as well as aging [ 22 ] and the overabundance of stored lipids in the liver. The downregulation of the pathway is estimated via the assessment of LC3II and autophagosomes, as well as the number of autophagolysosomes.…”
Section: The Association Between Autophagy and Nashmentioning
confidence: 99%
“…The transmembrane member 16A (TMEM16A) promotes the ubiquitination and degradation of glutathione peroxidase 4 (GPX4), thereby aggravating HIRI 9 . Due to older livers are more susceptible to lipid disorders and mitochondrial failure as well as iron ions further accumulate in the liver with age, we speculated that older livers are more prone to ferroptosis 10 . However, the role of ferroptosis in older HIRI is still unclear, and revealing the potential regulatory mechanism is critical for developing effective treatments to mitigate HIRI in the older.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy can control cell fate through distinct crosstalk signals (Xu et al, 2021). In many tissues, protective autophagy can be activated to inhibit cell apoptosis induced by stressors (Maiuri et al, 2007; Xue et al, 2016).…”
Section: Introductionmentioning
confidence: 99%